Phenomenological Study of Nginum Brem Reket Bontok: The Sasak Bayan Traditional Ritual in Bayan Beleq Village, North Lombok Regency, West Nusa Tenggara - Dirga, Dewa Made; Zaki, Lalu Ahmad (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
This research explores the phenomenon of